Biden's proposal for a US "sole purpose" nuclear declaratory policy: Consequences for allies in Asia, NATO and Germany - Liviu Horovitz; Claudia Major; Jonas Schneider; Lydia Wachs (Stiftung Wissenschaft und Politik (SWP), 2021)
US President Joe Biden is considering a change to US nuclear declaratory policy. Ever since the beginning of the nuclear age, Washington has stated that it could retaliate with a nuclear response to both nuclear and non-nuclear attacks. This declaratory policy may soon be restricted: President Biden would like to reduce the role of nuclear weapons through a 'sole purpose' (SP) declaration. Accordingly, the sole purpose of US nuclear weapons would be to deter and, if necessary, respond to nuclear attacks. The United States would pledge to never use nuclear weapons against conventional aggression. However, contrary to the expectations of SP proponents, this change would hardly reduce the nuclear risks that the United States face today. Moreover, US allies in Europe and Asia already fear that SP would diminish their security. For Germany specifically, it is worth asking what kind of political and military consequences an SP policy could have.
Keywords: 320